Petrogenesis of the tonalitic rocks from the Soer Rondane Mountains, East Antarctica - Ikeda, Yasuo; Shiraishi, Kazuyuki (National Institute of Polar Research, 1998)
P(論文) Tonalitic rocks (ca. 1000 Ma) from the Sor Rondane Mountains, East Antarctica, are characterized by relatively high Na_2O/K_2O (0.6-24), K/Rb (76-1638), Sr/Y (5-60), and (La/Yb) N (1-29), and relatively low CaO/ Na_2O (0.4-4) and low initial ^<87>Sr/^<86>Sr ratio (0.7024). They are chemically similar to trondhjemites (1000 Ma) from the Lutzow-Holm Complex and to Archean tonalite-trondhjemites. Trace element modeling of the partial melting of MORB suggests that tonalitic rocks were derived by partial melting of a basaltic source material under garnet amphibolite stability P-T conditions. We suggest that a young hot subducting plate along the S0r Rondane Mountains at 1000 Ma may have reached elevated temperatures which initiated melting of the slab and generated the tonalitic rocks. departmental bulletin paper